Physical fitness and anthropometrical profile of the Brazilian male judo team - Franchini, E.; Velly Nunes, A.; Morisson Moraes, J.; Boscolo del Vecchio, F. (Journal of Physiological Anthropology, 2007)
The present study had as objectives (1) to compare the morphological and functional characteristics of the male judo players of the Brazilian Team A (n=7) with the judo players of Teams B and C (reserves; n=15), and (2) to verify the association between the variables measured. Thus, 22 athletes from the seven Olympic weight categories were submitted to: a body composition evaluation (body mass, height, ten skinfolds, eight circumferences, three bone diameters and percent body fat estimation); the Special Judo Fitness Test (SJFT); maximal strength tests (one repetition-maximum, 1 RM, in bench press, row, and squat); and the Cooper test. One-way analysis of covariance was used to compare the groups. The relationships between variables were determined by the Pearson coefficient correlation. The significance level was fixed at 5%. No significant difference was found in any variable between them. The main significant correlations observed were between the following variables: VO2max and number of throws in the SJFT (r=0.79); percent body fat and estimated VO2max (r=-0.83) and number of throws in the SJFT (r=-0.70); chest circumference and bench press 1 RM (r=0.90) and in the row (r=0.80); and thigh circumference and squat 1 RM (r=0.86). However, there was no significant correlation between circumferences and 1 RM/kg of body mass. According to these results the main conclusions are: (1) the physical variables measured do not discriminate performance when analysis is directed to the best athletes; (2) a higher percent body fat is negatively correlated with performance in activities with body mass locomotion (Cooper test and the SJFT); (3) judo players with higher aerobic power performed better in high-intensity intermittent exercise; (4) judo players with bigger circumferences present bigger absolute maximal strength.